Study the effect of chlorpyrifos pesticide on genomic DNA in tissues (liver, kidney and brain) in adult male rats - WIJDAN THAMIR MAHDI,; MOHAMMED ALI MATLB, (International Journal of Pharma and Bio Sciences, 2017)
The present study aims to investigate the influence of the effect of treated pesticide of Chlorpyrifos 1 / 10 , 1 / 20, 1 / 30 mg / kg of body weight from the lethal dose LD50 of the pesticide , 0.1 ml per day for the periods of injections 14 days on some molecular and histological characteristics in male rats . Conformation corresponding single strand (PCR-SSCP) is the method used in order to detect for a genetic mutation in the Nephrin promoter gene to study the effectofChlorpyrifos on genomic DNA in the investigated organs tissues (liver, kidneyand brain) .Also been study histological changes of the organs mentioned. 24 adult male rats age of 65 days and the average of weights (125-135 g) have been assigned to four equal groups (6 per each); Intact control group (C) have been injected with normal saline.Treated groups have been injected withchlorpyrifos (CPF) (1 / 10, 1 / 20), 1 / 30 ) mg / kg. b .w i.p. ) for the periods 14 days.The results showed genetic mutation in the Nephrin promoter gene for a thread of DNA of investigated organs in treated groups as compared with that of intact control ( C ) groups for periods 14 days. Histological findings of Chlorpyrifos treated liver, kidney and brain tissue a clear impact on all of the tissues after the injection represented by the hepatic necrosis , congestion in the central vein , inflammation of the renal tubules and severe hemorrhage in the overall tissue of kidney and the expansion in the renal convoluted tubule. As the results showed bleeding in the brain tissue and the proliferation of astrocytes and glial cells with cerebral edema and a clear vascular congestion with partial congestion to the area or vacuum Vircho - Robin sp. around the vessel.It can be concluded that injection with pesticide leads to a mutation in Nephrin promoter gene with note some histological changes in liver, kidney and brain in male rats.